Bacteriophage T7 DNA polymerase – sequenase - Zhu, Bin (Frontiers in Microbiology, 2014)
An ideal DNA polymerase for chain-terminating DNA sequencing should possess the following features: 1) incorporate dideoxy- and other modified nucleotides at an efficiency similar to that of the cognate deoxynucleotides; 2) high processivity; 3) high fidelity in the absence of proofreading/exonuclease activity; and 4) production of clear and uniform signals for detection. The DNA polymerase encoded by bacteriophage T7 is naturally endowed with or can be engineered to have all these characteristics. The chemically or genetically modified enzyme (Sequenase) expedited significantly the development of DNA sequencing technology. This article reviews the history of studies on T7 DNA polymerase with emphasis on the serial key steps leading to its use in DNA sequencing. Lessons from the study and development of T7 DNA polymerase have and will continue to enlighten the characterization of novel DNA polymerases from newly discovered microbes and their modification for use in biotechnology.